Rationalization of technological criminology in the era of disruption - Supardi Hamid (Institute of Computer Science (IOCS), 2023)
In this era of disruption, the crime of manipulating electronic information, fraud, forgery or engineering using computer networks or the internet continues to grow. This study aims to examine the Rationalization of Criminology in Technology in the Disruption Era and Legal Reformulation in Preventing the Formation of Patterns of Criminological Rationalization in the World of Technology in the Disruption Era. With the formulation of the problem, namely the Rationalization of Criminology in the World of Technology in the Disruptive Era. Law Reformulation in Preventing the Formation of Criminological Rationalization Patterns in the World of Technology in a Disruptive Era. This research is a normative legal research with a statutory approach taken from secondary and tertiary data, which is then analyzed. The results of this study found that technology in the current era of disruption has significantly increased legal issues. So there is an urgency to carry out mapping as soon as possible to study criminology, which continues to this day. The contribution of this study is to provide an understanding and analysis of the problems related to the impact of the era of disruption and the influence of technology on the behavior of individuals and complex societies, so as to provide a basis for the government to reformulate the law more specific and detailed to prevent the formation of criminological rationalization patterns.